Gender and the second world war: lessons of war (Palgrave, 2017)
Showing how gender history contributes to existing understandings of the Second World War, this book offers detail and context on the national and transnational experiences of men and women during the war. Following a general introduction, the essays shed new light on the field and illustrate methods of working with a wide range of primary sources.